2023
DOI: 10.3390/jcm12185952
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Prognostic Nutritional Index and Chronic Microvascular Complications in Patients with Type 2 Diabetes Mellitus

Gulali Aktas

Abstract: The prognostic nutritional index (PNI) is associated with inflammatory conditions. Since type 2 diabetes mellitus (T2DM) and its microvascular complications produce a significant inflammatory burden, we aimed to compare the PNI levels of the subjects with T2DM to those of healthy individuals. Furthermore, we aimed to compare the PNI levels of the diabetic subjects, with and without microvascular complications. The study cohort consisted of T2DM patients and healthy volunteers. The general characteristics, labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Substantial evidence underscores the association between hematological markers and a spectrum of chronic disorders, inflammatory burdens, survival, and specific conditions, including infections, cardiac issues, diabetes mellitus, thyroid disorders, SARS-CoV-2 infections, and gastrointestinal diseases. [7][8][9][10][11][12][13][14][15][16][17][18] These studies [7][8][9][10][11][12][13][14][15][16][17][18] explored the connection of clinical conditions with markers such as the prognostic nutritional index (PNI), geriatric nutritional risk index (GNRI), and more recently hemogram-derived inflammation markers, including the neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR). These hematological markers have been associated with a poor prognosis and shorter survival.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence underscores the association between hematological markers and a spectrum of chronic disorders, inflammatory burdens, survival, and specific conditions, including infections, cardiac issues, diabetes mellitus, thyroid disorders, SARS-CoV-2 infections, and gastrointestinal diseases. [7][8][9][10][11][12][13][14][15][16][17][18] These studies [7][8][9][10][11][12][13][14][15][16][17][18] explored the connection of clinical conditions with markers such as the prognostic nutritional index (PNI), geriatric nutritional risk index (GNRI), and more recently hemogram-derived inflammation markers, including the neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR). These hematological markers have been associated with a poor prognosis and shorter survival.…”
Section: Introductionmentioning
confidence: 99%
“… 31 Diabetes mellitus and its microvascular complications are associated with high burden of inflammation. 32 , 33 Given the central role of inflammation in DN, it is logical to investigate autophagy, pyroptosis, and ferroptosis in the context of this disease. Elucidating the contributions of these cellular processes in DN may offer valuable insights into potential therapeutic strategies for managing this condition.…”
Section: Introductionmentioning
confidence: 99%
“… 10–12 Additionally, risk factors for the occurrence and development of coronary artery disease are closely associated with inflammation. 13–15 Acute myocardial infarction (AMI), a severe acute coronary event, has been shown to play a crucial role in inflammation during its occurrence and development. 16–18 Recent clinical studies have confirmed that anti-inflammatory drugs can reduce the residual risk of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%